Pengadaan Fasilitas Pendidikan Melalui Zakat Infak Sedekah dan Wakaf (ZISWAF) di SD Juara Kota Bandung - Ni’mawati; Mohamad Erihadiana (STAI Siliwangi Bandung, 2020)
This research is motivated by a preliminary study by the author that in the city of Bandung there is a good quality school but free of charge, namely SD Juara, this school is free because it is funded by zakat, infak, sedekah, and wakaf (ZISWAF). SD Juara has adequate educational facilities and attracts the interest of the community to send their children to the place even though they have to pay. In this study the authors used a descriptive analysis method, through the study of documentation, observation and interviews. The study focused on the availability of educational facilities in SD Juara, the facility procurement program, and the ZISWAF RZ Program in the provision of educational facilities. The conclusions of this study are: 1) educational facilities in SD Juara have met the minimum standards set by the government; 2) the education facility procurement program at SD Juara was initially one hundred percent through ZISWAF funds and starting in the 2019 the procurement facilities of SD Juara was charged to students; and 3) The ZISWAF RZ program in the provision of educational facilities for SD Juara was initially initiated and implemented by Rumah Zakat because SD Juara is part of the four flagship programs of Rumah Zakat, namely champion smile, stand smile, healthy smile, and sustainable smile. Next, the ZISWAF program is only intended for 20% of students from the poor, while the provision of other facilities starting in the 2019 is charged to students, from BOS funds and from non-binding donors.